Chapter 4 Nursing a plague: nurses' perspectives on their work during the United Kingdom HIV/ AIDS crisis, 1981- 96 - Dickinson, Tommy (Manchester University Press, 2022)
As part of the United Kingdom's response to the escalating HIV/AIDS crisis during the 1980s, special wards and community-based services were established to care for people living with HIV/AIDS (PWHA).  Much of the pioneering and innovative care developed at these centres can be attributed to nurses. However, UK nursing history has hitherto neglected to tell their stories. This chapter rectifies this omission by drawing on a wealth of source material including previously unseen, enlightening, and frequently moving oral histories, as well as archival and news media sources, to explore the actions and perceptions of the UK nurses who cared for PWHA, alongside the reflections of PWHA and their loved ones who received this care. This chapter reveals how assertive PWHA took control of their own care, often becoming experts on their condition - a phenomenon that challenged ideas of medical paternalism by reclaiming decision-making power in the name of the patient.  We explore questions of ethics and socialisation by analysing how nurses were similarly tasked with deciding what actions were permissible in times of crisis - decisions made along the frequently blurred lines that this crisis drew between private and professional lives. Appreciating the personal draw that HIV/AIDS care had to nurses who identified as queer in particular, and the sense of duty this often evoked, offered a meaningful way of interpreting the research gathered for this chapter.  Last, this makes an important contribution to the documented history of nurses' experiences and constructions of the care of individuals belonging to stigmatised groups.